Survey of Obstetrician-Gynecologists about Giardiasis - Amy Krueger; Jay Schulkin; Jeffrey L. Jones (Hindawi Limited, 2007)
Giardiasis is one of the most common parasitic diseases in the United States with over 15 400 cases reported in 2005. A survey was conducted by The American College of Obstetricians and Gynecologists (ACOG) in collaboration with the Centers for Disease Control and Prevention (CDC) to evaluate the knowledge of obstetricians and gynecologists regarding the diagnosis and treatment of giardiasis. The questionnaire was distributed to a random sample of 1200 ACOG fellows during February through June of 2006. Five hundred and two (42%) responded to the survey. The respondents showed good general knowledge about diagnosis, transmission, and prevention; however, there was some uncertainty about the treatment of giardiasis and which medications are the safest to administer during the first trimester of pregnancy.